Integrating the Values of the Oral Tradition Dongdonan Salapan Wali Puhun as an Ethnopedagogical Model for Indonesian Language and Literature Learning in Grade VI of SDN Mandalajaya, Balegede Village, Naringgul Subdistrict, Cianjur Regency - Saep Lukman; Iis Ristiani; Neng Wina Resky Agustina (Universitas Muhammadiyah Enrekang, 2025)
This study develops an ethnopedagogical learning model for Indonesian Language and Literature by utilizing the cultural values embedded in the oral tradition Dongdonan Salapan Wali Puhun as a primary learning resource. The main objective is to produce a valid, practical, and effective learning model to enhance cultural literacy, text comprehension skills, and character formation among Grade VI students at SDN Mandalajaya, Balegede Village, Naringgul Subdistrict, Cianjur Regency. The research employs a Research and Development (R&D) approach based on the Borg & Gall model, streamlined into seven stages: needs analysis, cultural value exploration of Dongdonan, model design, expert validation, limited trial implementation, model revision, and wider field testing. The needs analysis revealed a low utilization of local cultural resources in Indonesian language instruction, despite the students’ social environment remaining closely connected to the cultural practices of Miduana Indigenous Village. The cultural value study identified that Dongdonan Salapan Wali Puhun contains nine symbolic entities that embody values such as leadership, purity, wisdom, courage, fertility, and ecological ethics—attributes aligned with the Profile of Pancasila Students. Expert validation indicated high feasibility in terms of content, construct, language, and pedagogical aspects. Both limited and extensive trials demonstrated improvements in students’ text comprehension, creativity, cooperation, and motivation to learn Indonesian. The study concludes that integrating Dongdonan Salapan Wali Puhun into an ethnopedagogical learning model is effective in strengthening students’ cultural literacy and character development. The developed model is applicable in rural elementary schools with similar cultural contexts and is recommended as an educational innovation supporting the implementation of the Merdeka Curriculum.